Role of Secreted Frizzled-Related Protein 1 in Early Mammary Gland Tumorigenesis and Its Regulation in Breast Microenvironment - Alisson Clemenceau; Caroline Diorio; Francine Durocher (Cells, 2020)
In mice, the lack of secreted frizzled-related protein 1 (SFRP1) is responsible for mammogenesis and hyperplasia, while, in bovines, its overexpression is associated with post-lactational mammary gland involution. Interestingly, there are no reports dealing with the role of SFRP1 in female involution. However, SFRP1 dysregulation is largely associated with human tumorigenesis in the literature. Indeed, the lack of SFRP1 is associated with both tumor development and patient prognosis. Considering the increased risk of breast tumor development associated with incomplete mammary gland involution, it is crucial to demystify the “grey zone” between physiological age-related involution and tumorigenesis. In this review, we explore the functions of SFRP1 involved in the breast involution processes to understand the perturbations driven by the disappearance of SFRP1 in mammary tissue. Moreover, we question the presence of recurrent microcalcifications identified by mammography. In bone metastases from prostate primary tumor, overexpression of SFRP1 results in an osteolytic response of the tumor cells. Hence, we explore the hypothesis of an osteoblastic differentiation of mammary cells induced by the lack of SFRP1 during lobular involution, resulting in a new accumulation of hydroxyapatite crystals in the breast tissue.